Fabrication of ZnO nanosheets self-assembled by nanoparticles for accelerated electrocatalytic reduction of CO2 to CO. (1st February 2023) - Wang, Hongtao; Xiao, Yuanyuan; Qi, Yu; Zhang, Aiming; Du, Jianping; Li, Jinping; Guo, Tianyu
Highlights: ZnO nanosheets self-assembled by nanoparticles were achieved by a facile solvothermal method. The obtained ZnO-UR electrocatalyst possessed higher surface area and more activity sites. The ZnO-UR material exhibited superior electrocatalytic activity and selectivity of CO. This study provides a new perspective for the fabrication of efficient electrocatalysts in the field of CO2 RR. Abstract: Electrocatalytic conversion of carbon dioxide into value-added chemicals is an effective technology to respond positively to carbon neutrality policies. Zinc oxide (ZnO) is considered as a promising catalyst for electrochemical reduction of CO2 . Herein, a series of ZnO electrocatalysts were prepared by a facile solvothermal method, whose structures were tuned by changing alkaline additives and molar ratios of zinc source/urea. The electrocatalytic property for CO2 reduction was explored in detail. Among them, the ZnO nanosheets self-assembled by ultrasmall nanoparticles prepared using urea (ZnO-UR) and the molar ratio (1:2) of zinc source/urea deliver the superior property with 88 % CO faradic efficiency at −0.95 V vs RHE in KHCO3 electrolyte. The outstanding property can be attributed to the rough surface, rich mesoporous structure, more activity sites and faster electron transfer. Moreover, boosted FECO (98 %) can be obtained in the KCl electrolyte at the same applied potential. This work provides a straightforward way to control the electrocatalytic activity and selectivity of CO2 RR through adjusting alkaline additives and contents.